Synthesis of Heat-Integrated Resource Conservation Networks - Tan, Yin Ling; Ng, D.; El-Halwagi, M.; Samyudia, Yudi; Foo, D. (Elsevier, 2012)
The current drive towards environmental sustainability, the rising costs of energy, fresh resources as well as waste treatments have forced process industries to pay much attention on the improvement of their processes. Consequently, significant efforts have been devoted to develop systematic techniques for heat conservation and waste reduction. In the past, the synthesis of optimal resource conservation network (RCN) has been dealt independently for single resource. To date, very little has been accomplished on the use of heuristic techniques for simultaneous heat and resource conservation. In this work, a novel methodology is developed for the synthesis of RCN, focusing on simultaneous heat and mass integration. With the newly developed methods, the minimum resources consumption and waste generation can be identified. A case study is utilised to demonstrate the applicability of the methodology.